Mutation analysis of exon1 of bone morphogenetic protein-15 gene in Iranian patients with polycystic ovarian syndrome - Anahita Mehdizadeh; Mohammad Hasan Sheikhha; Seyed Mehdi Kalantar; Bibi Shahnaz Aali; Azam Ghanei (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: With the prevalence of 6-10%, polycystic ovarian syndrome (PCOS) is considered the most common endocrinological disorder affecting women in their reproductive age. It has been suggested that genetic factors participate in the development of PCOS. Follicular development has been considered as one of the impaired processes in PCOS. Bone morphogenetic protein-15 (BMP-15) gene is a candidate gene in follicular development and its variants may play role in pathogenesis of PCOS. Objective: To investigate whether BMP-15 gene mutations are present in Iranian women with PCOS. Materials and Methods: In this cross-sectional study 5 ml venous blood samples was taken from 70 PCOS women referring to Afzalipour Hospital, Kerman University of Medical Sciences, Kerman, Iran, between January to December 2014. Genomic DNA was extracted from the blood sample by salting out method. Then a set of PCR reactions for exon1 of BMP-15 gene was performed using specific primers followed by genotyping with direct sequencing. Results: Two different polymorphisms were found in the gene under study. In total 20 patients (28.6%) were heterozygote (C/G), and 2 patients (2.86%) were homozygous (G/G) for c.-9C>G in 5´UTR promoter region of BMP-15 gene (rs3810682). In addition, in the coding region of exon1, three patients (4.3%) were heterozygote (G/A) for c.A308G (rs41308602). Two PCOS patients (2.86%) appeared to have both c.-9C>G (C/G) and c.A308G (G/A) variants simultaneously. Conclusion: Our research detected two polymorphisms of BMP-15 gene among PCOS patients, indicating that even though it cannot be concluded that variants of BMP-15 gene are the principal cause of polycystic ovarian syndrome; they could be involved in pathogenic process in development of PCOS.